Serum brain-derived neurotrophic factor (BDNF) in sleep-disordered patients: relation to sleep stage N3 and rapid eye movement (REM) sleep across diagnostic entities - Deuschle, Michael; Schredl, Michael; Wisch, Christian; Schilling, Claudia; Gilles, Maria (Journal of sleep research, 2018)
Experimental and clinical evidence suggests an association between neuroplasticity, brain-derived neurotrophic factor and sleep. We aimed at testing the hypotheses that brain-derived neurotrophic factor is associated with specific aspects of sleep architecture or sleep stages in patients with sleep disorders. We included 35 patients with primary insomnia, 31 patients with restless legs syndrome, 17 patients with idiopathic hypersomnia, 10 patients with narcolepsy and 37 healthy controls. Morning serum brain-derived neurotrophic factor concentrations were measured in patients and controls. In patients, blood sampling was followed by polysomnographic sleep investigation. Low brain-derived neurotrophic factor levels were associated with a low percentage of sleep stage N3 and rapid eye movement sleep across diagnostic entities. However, there was no difference in brain-derived neurotrophic factor levels between diagnostic groups. Our data indicate that serum levels of brain-derived neurotrophic factor, independent of a specific sleep disorder, are related to the proportion of sleep stage N3 and REM sleep. This preliminary observation is in accordance with the assumption that sleep stage N3 is involved in the regulation of neuroplasticity.